The natural economic science : re-writing economic fundamentals - Fudulu, Paul (Emerald Publishing, 2019)
Economics is widely regarded as a social science. In this ground-breaking new study, Paul Fudulu crosses the divide between natural and social science to introduce a new theory of natural economic science, based on one of the most important causal laws of physics: the entropic degradation of the universe.